Selective Photocatalytic Carbon Dioxide Reduction by a Reduced Molybdenum‐Based Polyoxometalate Catalyst. Issue 2 (26th November 2018) - Barman, Soumitra; Sreejith, S. S.; Garai, Somnath; Pochamoni, Ramudu; Roy, Soumyajit
Abstract: Currently, photochemical carbon dioxide reduction is a most sought‐after process as it involves the simultaneous removal of greenhouse CO2 gas and the production of useful products. In this study, we report the selective formation of formaldehyde in photochemical carbon dioxide reduction using a reduced polyoxometalate (POM) based catalyst. By simply tuning the redox state of the metal centre in the POM, we can obtain the more reduced product formaldehyde from carbon dioxide. As a result of the high Mo V /Mo VI ratio in the cluster, formaldehyde is obtained as the major product as opposed to formic acid. Since the catalyst POM 1 itself readily absorbs light, no external photosensitizer is used. In the reduction process of carbon dioxide, water acts as the electron donor and is oxidized to oxygen rendering the whole process viable and green. (1 =Mo16 =[(CH3 )NH2 4 (Mo V 2 O4 )6 (μ2 ‐OH)10 (μ2 ‐O)2 (μ3 ‐OH)2 (μ3 ‐O)2 (Mo VI O3 H)4 ]0.94 [(Mo V 2 O4 )6 (μ2 ‐OH)10 (μ2 ‐O)2 (Mo VI O3 H)4 Mo VI (μ3 ‐O)4 ]0.06 ). Abstract : Less is more : Efficient photoreduction of carbon dioxide to produce value‐added liquid products was achieved using a reduced molybdenum‐based polyoxometalate. A high Mo V :Mo VI ratio results in the enhanced production of formaldehyde over formic acid.